PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION PADA PT SAMCO FARMA KOTA TANGERANG - Anariesti Melanie Salsabila; Kemas Vivi Andayani (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine whether there is an influence between compensation and organizational culture on employee turnover intention at PT Samco Farma, Tangerang City. The method used is an associative research type with a quantitative approach. There are 80 respondents as samples. Data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, determination coefficient analysis and hypothesis testing. The results of this study are that location and promotion have a significant effect on purchasing decisions with the regression equation Y = 11.911 + 0.305X1 + 0.435X2. with a correlation value of 0.778 and a coefficient of determination value of 60.6% while the remaining 39.4% is influenced by other factors. The t test shows that the t_count value is 3.105 > t_table 1.991 with a significance of 0.003 < 0.05. Partially there is a significant influence of the compensation variable on turnover intention. The t test shows that the t¬_count value is 4.802 > t_table 1.991 with a significance of 0.000 < 0.050. Partially there is a significant influence of organizational culture variables on turnover intention. The F test shows that the F_count value is 59.163 > F_table value 3.115, reinforced by pvalue < Sig 0.05 (0.000 < 0.05), indicating that there is a simultaneous positive and significant influence between compensation and organizational culture on turnover intention at PT Samco Farma Tangerang City.